ANTHROPOMETRY, CORPORAL COMPOSITION AND PHYSICAL TYPE OF YOUNG FEMININE PARAIBAN TEAM 2007 OF BASKETBALL (Fiep Bulletin - online, 2014)
This study it has as objective to compare the anthropometrics characteristics, corporal composition and somatotipo of the athletes of the feminine youthful paraibana election of 2007 and for position of game. Materials and methods: 15 pertaining feminine athletes to the paraibana election of basketball was evaluate for method anthropometric. In the analysis of the components of somatotipo multivaried analysis of variance was used (MANOVA). The established level of significance was p< 0,05. Results. The components of somatotipo of the sections, pivots and shipowners had not presented significant differences F6,20= 2,023) with Wilks `ë= 0,387. The sections had been classified as endomorfo balanced (2.4-3.0-3.7), the pivots had been classified as endomorfo mesomorfico (3.4-3.3-3.4) and the shipowners as endomorfo mesomorfico (2.6-3.9-2.9). Conclusion. The Somatotipo of all the athletes was characterized as endomorfo mesomorfico.
Keywords: Anthropometry; basketball; body composition; somatotype